Concurrence of Juvenile Idiopathic Arthritis and Multiple Sclerosis - Kaouther, Ben Abdelghani; Leila, Souabni; Salwa, Belhadj; Leith, Zakraoui (Case Reports in Rheumatology, 2011)
We report a 21-year-old female patient known to have Juvenile idiopathic arthritis (JIA) who later developed multiple sclerosis (MS). The disease was documented on the brain and cerebral magnetic resonance imaging (MRI) and the visual evoked potential. Our case emphasizes the need to evaluate the symptoms and brain MRI carefully. The concurrence of MS and JIA is uncommon. The possible relationship between the 2 diseases was discussed.